2018
DOI: 10.1080/0284186x.2018.1438657
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence and survival of head and neck cancers in Denmark: a nation-wide study from 1980 to 2014

Abstract: This nation-wide study showed a significant rise in incidence of HNC for men and women along with a significant increase in relative survival. Oropharyngeal cancer had the highest increase in incidence followed by hypopharyngeal cancer which showed the poorest survival of HNCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
54
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 28 publications
12
54
3
Order By: Relevance
“…An equal number of men and women participated, which does not reflect the actual distribution of HNC in the Danish population, where HNC more frequently affects men than women [3]. This could potentially have affected the representativeness of our study population.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…An equal number of men and women participated, which does not reflect the actual distribution of HNC in the Danish population, where HNC more frequently affects men than women [3]. This could potentially have affected the representativeness of our study population.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…Annually, approximately 900,000 people worldwide are diagnosed with HNC [2] making it a substantial contributor to morbidity and mortality. The incidence but also the survival has increased during recent years [3]. Hence, the population of HNC survivors is increasing and so is the requirement for appropriate rehabilitation services [4].…”
Section: Introductionmentioning
confidence: 99%
“…The survival rates for head and neck cancer vary depending on the site involved (7). Previous European and American population-based studies reported that the 5-year relative survival of German people with OC diagnosed in 2002-2006 was 54.6% (8), whereas that of Danish people with head and neck cancer was 62.4% (2010-2014) (9). For American individuals with cancer in the oral cavity, oropharynx, and subsites (base of tongue, hard palate, tonsil, etc.…”
Section: ' Introductionmentioning
confidence: 99%
“…The incidence of head and neck cancer (HNC) has increased to approximately 900.000 new cases worldwide in 2018 [1,2]. With a simultaneous increase in the relative survival [3], the population of patients treated for HNC is increasing.…”
Section: Introductionmentioning
confidence: 99%